Broadband and high‐efficiency conversion from guided waves to spoof surface plasmon polaritons. Issue 1 (22nd November 2013) - Ma, Hui Feng; Shen, Xiaopeng; Cheng, Qiang; Jiang, Wei Xiang; Cui, Tie Jun
<x xml:space="preserve">Abstract</x> The conversion from spatial propagating waves to surface plasmon polaritons (SPPs) has been well studied, and shown to be very efficient by using gradient‐index metasurfaces. However, feeding energies into and extracting signals from functional plasmonic devices or circuits through transmission lines require the efficient conversion between SPPs and guided waves, which has not been reported, to the best of our knowledge. In this paper, a smooth bridge between the conventional coplanar waveguide (CPW) with 50 Ω impedance and plasmonic waveguide (e.g., an ultrathin corrugated metallic strip) has been proposed in the microwave frequency, which converts the guided waves to spoof SPPs with high efficiency in broadband. A matching transition has been proposed and designed, which is constructed by gradient corrugations and flaring ground, to match both the momentum and impedance of CPW and the plasmonic waveguide. Simulated and measured results on the transmission coefficients and near‐filed distributions show excellent transmission efficiency from CPW to a plasmonic waveguide to CPW in a wide frequency band. The high‐efficiency and broadband conversion between SPPs and guided waves opens up a new avenue for advanced conventional plasmonic integrated functional devices and circuits. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>